2019
DOI: 10.1002/poi3.220
|View full text |Cite
|
Sign up to set email alerts
|

Does Aid for Information and Communications Technology Help Reduce the Global Digital Divide?

Abstract: The Aid for Trade (AfT) initiative was launched at the 2005 World Trade Organization Ministerial Conference with the aim of helping developing countries develop their trade capacity and better integrate into the global trade system. This article examines the impact of Aid for Information and Communications Technology (ICT) (a component of AfT) on the global digital divide of recipient countries, measured by the Internet penetration rate (i.e., the proportion of individuals using the Internet in a given country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The digital economy forms a gathering situation in the virtual space, allowing for openness, sharing, penetration, and diffusion (Cui et al, 2020; Gnangnon, 2019; Tranos et al, 2021) and becoming an irresistible trend. The openness and sharing of digital economy agglomeration optimizes the matching and trading of products; accelerates the communication and dissemination of knowledge, information, and technology; and broadens the breadth and depth of interregional economic activities.…”
Section: Mechanism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The digital economy forms a gathering situation in the virtual space, allowing for openness, sharing, penetration, and diffusion (Cui et al, 2020; Gnangnon, 2019; Tranos et al, 2021) and becoming an irresistible trend. The openness and sharing of digital economy agglomeration optimizes the matching and trading of products; accelerates the communication and dissemination of knowledge, information, and technology; and broadens the breadth and depth of interregional economic activities.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…While automation replaces some labor positions, it also creates new jobs with more comparative advantages, thereby improving production efficiency (Acemoglu & Restrepo, 2018). As a result of the penetration and diffusion of digital economy agglomeration, the knowledge spillover effect is strengthened (Gnangnon, 2019), a convenient information exchange platform is provided, product matching and trading are optimized, information interaction is accelerated (Barata et al, 2018), the contradiction between supply and demand in social production is eliminated, high-quality economic development is promoted, and inclusive green development is ultimately supported. ICT, such as the Internet and IoT, promotes a high degree of integration of the physical world, cyberspace, and the network of production relations (Contador et al, 2020); breaks through the technical, interest, and institutional boundaries existing in the real world; effectively alleviates the inhibitory effect on production efficiency caused by factor congestion; and helps to increase total output.…”
Section: Digital Economy Agglomeration Economic Growth and Inclusive ...mentioning
confidence: 99%
“…As a result, through these channels, innovation can introduce new export products or expand the range of goods and services that a country can produce and export (e.g., Dollar, 1986; Grossman & Helpman, 1989; Krugman, 1979), and hence promote services export diversification. From an empirical perspective, Gnangnon (2019e) has provided empirical evidence that higher AfT inflows for ICT induce a rise in the internet penetration rate and help reduce the internet related gap with respect to other countries in the world, although this effect has appeared to be more important for advanced AfT recipient countries compared to relatively less advanced countries. In the meantime, Chen (2013) has demonstrated that innovation (measured by patents counts) stimulates both the extensive margins (i.e., the number of products exported from a country) and the intensive margins (i.e., the export value of each product from a country).…”
Section: Theoretical Discussion On How Aft Flows Could Affect Services Export Diversificationmentioning
confidence: 99%
“…The effectiveness of AfT flows has also been evaluated with respect to several macroeconomic indicators in recipient countries. These include trade policy and tariff policy volatility (e.g., Gnangnon, 2018;Gnangnon, 2019b;Hoekstra & Koopmann, 2012), export product diversification/economic complexity (e.g., Gnangnon, 2019cGnangnon, , 2019dKim, 2019), reduction of the digital divide (e.g., Gnangnon, 2019e); whether the launch of the AfT initiative have genuinely increased resource flows (e.g., Gnangnon, 2019f); submission of trademarks applications (e.g., Gnangnon, 2019g); employment promotion (e.g., Gnangnon, 2019h) and employment diversification (e.g., Gnangnon, 2019i); trade tax revenue (e.g., Gnangnon, 2016); and FDI inflows (e.g., Lee & Ries, 2016;Ly-My & Lee, 2019). To the best of our knowledge, among those studies, in particular the ones that have looked at the effect of AfT on recipient countries' trade performance, only four studies (Ghimire et al, 2013;Gnangnon & Ramirez-Ramirez, 2020;Hoekman & Shingal, 2020;Martinez-Zarzoso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3.3.6 On the global digital divide. Gnangnon (2019f) analysed the effect of AfT Information and Communications Technology (ICT) (an element of AfT for economic infrastructure) on recipient countries' global digital as defined by the rate of internet adoption (the number of internet users per 100 individuals who can connect to the global network) and the internet penetration distance (the disparity in internet penetration rates between a country and the worldwide average). Panel data from 119 recipient nations was used to conduct the empirical analysis, covering the years 2004-2015.…”
Section: Aid For Trade Initiative 16 Years Onmentioning
confidence: 99%